Estrategias de educación emocional para disminuir conductas disruptivas en los estudiantes del octavo año de educación básica de la unidad educativa José Ingenieros Loja periodo 2018-2019. - Gomez Jimenez, Stefany Katherine (2019)
Disruptive behavior is a problem of discipline in the classroom that seriously affects the educational and personal development of the student, for this reason the present thesis entitled EMOTIONAL EDUCATION STRATEGIES TO REDUCE DISRUPTIVE BEHAVIORS IN THE STUDENTS OF THE EIGHTH YEAR OF BASIC EDUCATION OF THE EDUCATIONAL UNIT JOSÉ INGENIEROS DE LA CIUDAD DE LOJA PERIOD 2018- 2019. Its objective is to implement emotional education strategies the presence of disruptive behavior in the classroom. The study is descriptive, pre-experimental design, cross-sectional, the methods that were used: scientific, deductive, inductive, analytical-synthetic. The questionnaire was applied to measure disruptive behaviors (CCDEF). The sample object of study corresponds to 24 students. The results of the pre-test were: Aggressiveness 38% in the indicator sometimes, irresponsibility 37% frequently, disobedience of the norms 44% frequently, disruptive of the environment class 32% frequently, under personal self-control 39% with frequency. After the application of the proposal the results of the post-test were: aggressiveness 46% in the indicator never, irresponsibility 47% almost never, disobedience of the norms 47% never, disruptive of the classroom environment 50% never and under personal self-control 60% almost never. Likewise, an 89% acceptance of the applied proposal was obtained. Concluding that students decreased in large quantities the presence of disruptive behavior, this is why it is considered necessary to continue using different emotional education strategies to solve this behavioral problem in students